Estudio morfológico de Aleuropleurocelus abnormis (Quaintance) (Hemiptera: Aleyrodidae) y nuevos registros de especies del género para México - Carapia-Ruíz, Vicente Emilio; Sánchez-Flores, Oscar Ángel; García-Martínez, Oswaldo; Castillo-Gutiérrez, Antonio (Instituto de Ecología, A.C., 2018)
Aleuropleurocelus abnormis (Quaintance, 1900) is a whitefly of the subfamily Aleurodinae which was poorly studied in its initial classification, this study gives a detailed description for the current state and development of the taxonomy of the genus. The specimens used were from different states of Mexico and the USA, the morphological characteristics are illustrated by means of digital photography and differences are discussed with A. nevadiensis and with others not classified. A. abnormis was found in herbarium in a species of Quercus with tag Collection of Louisiana USA. A new record of A. hyptisemoryi for Baja California Sur and Baja California México is reported on Hyptis emoryii and Hipis albida.